THE INFLUENCE OF STOCK TRADING VOLUME AND COMPANY SIZE ON STOCK PRICE VOLATILITY IN IDX80 BANKING COMPANIES DURING THE COVID-19 PANDEMIC - Eko Putra; Mahdahleni Mahdahleni; Mia Muchia Desda (Jurnal Ekonomi, 2022)
This study was conducted to determine the effect of stock trading volume and company size on stock price volatility in IDX80 Banking Companies during the Covid-19 Pandemic. The place and time of the author's research was carried out on banks listed on the Indonesia Stock Exchange starting from 2020 to 2021. The population of this study was a banking company listed on the IDX in 2020 and 2021. The sample in this study used the sampling technique, namely Purposive Sampling. The results of the study found that the results of the analysis with panel data regression, namely Y = 17.49811 + 0.552606 - 0.853274 showed that the Stock Trading Volume had a positive effect of 0.552606 and not significant at 0.6997 > 0.05. The technique used is panel data regression. The results showed that: (1) Stock trading volume had a positive and insignificant effect on stock price volatility. (2) Firm size has a negative and significant effect on stock price volatility. (3) Stock trading volume and firm size have a positive and significant effect on stock price volatility.